CLASSIFICATION AND CHARACTERIZATION OF FAMILY CATTLE FARMING SYSTEMS OF THE FRAILESCA REGION OF CHIAPAS, MEXICO, CONSIDERING THE CONTRIBUTION OF CATTLE RAISING TO FAMILY INCOME - José Roberto Aguilar Jiménez; Carlos Ernesto Aguilar Jiménez; Francisco Guevara Hernández; José Galdámez Galdámez; Franklin Berlán Martínez Aguilar; Manuel Alejandro La O Arias; Hernán Orbelin Mandujano Camacho; Mario Alberto Abarca Acero; José Nahed Toral (Tropical and Subtropical Agroecosystems, 2023)
Background: In recent decades, many peasant regions of southeastern Mexico, have undergone an expansion of cattle raising. This has led to farmers transitioning from crop agriculture toward mixed production or specializing in cattle raising. Characterizing livestock systems using a multidimensional perspective allows for identifying strategies for increasing their sustainability. Objective: To classify and characterize family cattle farming systems (FCFS) of the Frailesca region of Chiapas, Mexico taking into account the contribution of cattle raising to family income, and using a multidimensional perspective. Methodology: Eighty family units in two areas of the Frailesca region - valley (40) and highlands (40) - were evaluated. Information was obtained through application of questionnaires to farmers. According to the percentage of contribution of cattle raising to family income, a K-means clustering analysis was carried out in each area to differentiate FCFS. Average values of technical, economic, environmental, and social indicators were compared among systems using ANOVA or Kruskall Wallis tests. Results: Two FCFS were identified in each of two areas of the Frailesca region: (I) mixed family systems (MFS) and (II) family systems specialized in cattle raising (FSSC). Average percentages of contribution of cattle raising to family income were: (1) valley MFS = 32.5%; (2) valley FSSC = 80.5%; (3) highland MFS = 38.5%; and (4) highland FSSC = 71.7%.  The valley FSSC followed an intensive-technified cattle raising with high use of external inputs and had the highest values of the economic indicators: calves produced per ha, milk production per cow, and net margin per hectare. The valley MFS practiced semi-intensive-technified cattle raising with low use of external inputs which led it had lower economic profitability than that of the valley FSCC. In both highland systems, farmers followed extensive cattle raising with low use of external inputs. For the economic dimension, these were similar to that of the valley MFS. Nevertheless, for the environmental dimension both highland systems were better (diversity of grasses, backyard animals, cattle breeds, and woody fodder crops) than the valley systems. Particularly, the highlands MFS had the greatest proportion of forested land and grasslands with scattered trees, as well as the abundance of wild fauna. For the social dimension, both the FSSC had a higher level of technical assistance and training, less dependence on subsidies, and a greater capacity to cover their basic purchased-food costs than the two MFS. The highlands MFS had the highest number of family beneficiaries, while the highlands FSSC had a higher level of membership in farmers´ organizations than did both types of valley systems. Implications: The valley farmers should reduce their environmental impacts and maintain and even increase productivity, in the case of the mixed family system. The highlands farmers should increase productivity, and reduce their dependence on subsidies. Conclusions: In order to overcome the multidimensional limitations and increase the sustainability of family cattle raising systems, it is necessary that external social actors promote agroecology and silvopastoral systems, as well as the famers´ co-responsibility and active participation along the process.